Role of laparoscopy in infertility in a rural setup hospital - Samal, Sawaranalata; Agrawal, Sweta; Agrawal, Madhuprita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Infertility is a major health issue with multifactorial etiology. None of the laboratory findings alone is conclusive in diagnosing infertility. A minimally invasive method such as laparoscopy has come into play in finding the etiology and planning the further management of infertility. This study is intended to focus the role of laparoscopy in finding the causes of infertility in a rural set up area. Methods: 100 cases of primary and secondary infertility were subjected to laparoscopy after taking informed consent. Causes of infertility were found out. The present study was conducted at Acharya Vinoba Bhave Rural Hospital, Wardha from 2011-2013. Results: There were 75 cases (75%) of primary infertility as against 25 cases (25%) of secondary infertility. A maximum of 40 cases (40%) were in the age group of 20 - 25 years. Uterine causes contributed about 14 cases (14%), tubal causes contributed about 34 (34%), ovarian factors accounted for 27 cases (27%), peritoneal causes contributed for 7 cases (7%), unexplained infertility accounted for 18 cases (18%). Conclusions: Laparoscopy is a gold standard for tubal, ovarian cases, in cases of endometriosis and in adhesions till date. Laparoscopy can be used for evaluation of almost all the cases of infertility. Because of its potential diagnostic and therapeutic benefits, all the patients with infertility should undergo laparoscopy prior to any advance procedure in infertility management. Diagnostic laparoscopy has become so important in the evaluation of infertility that it has now been considered as a basic skill which should be learnt by every gynaecologist in the advanced scientific era.